AB0108B PREVALENCE AND RISK FACTORS INFLUENCING THE DEVELOPMENT OF ARTERIAL HYPERTENSION IN PATIENTS WITH A GOUT. (June 2019) - Markelova, Eugenia; Novikova, Diana; Eliseev, Maxim; Popkova, Tatiana; Glukhova, Svetlana
Abstract : Background: Cardiovascular diseases (CVD) is the leading cause of death for gout. Arterial hypertension (AH) is a proven CVD risk factor (CVD-RF). Objectives: To assess the factors influencing on development of an AH in patients with a gout. Methods: 286 male patients fulfilling Wallace proposed criteria for gout were included in the study: age 51.2 [42.8;59.4] years (ys), disease duration – 6.2 [3.8;12.1] ys, number of joints involved during disease course – 7[4;12], subcutaneous tophi – in 35% pts, intraosseous tophi – in 44% pts, nephrolithiasis – in 69% pts, abdominal obesity – in 71%. All pts underwent standard clinical examination, C-reactive protein (CRP), total cholesterol (TC), triglycerides (TG), low and high density lipoproteins (LDL/HDL), serum uric acid, serum creatinine, smoking, family history of AH, body mass index (BMI), diabetes mellitus was performed by standard procedure. We estimated the adjusted odds ratio (OR) and 95% confidence interval (95% CI). Results: There were two groups of patients with AH diagnosed on clinical data: group 1 (with AH) - 244 (85%) pts, group 2 (without AH) - 42 (15%) pts. The 1 st group pts were older (52.3[44.5; 61.1] vs 41.9[38.3; 50.1] ys), had longer duration of gout (6.7[3.9; 13.7] vs 4.5[3; 7.9]), a higher number of joints involved during disease course (8[4; 12] vs 5[3; 9]). The frequency of family history of AH (68.3% vs 48.8%), abdominal obesity (55.3% vs 33.3%), nephrolithiasis (71% vs 54.7%), intraosseous tophi (48% vs 21%) was higher in group 1 as compared with group 2, p<0, 05. BMI and CRP level was higher in group 1 compared with group 2: 30.2[27.4; 33.1] vs 27.9[26.3; 30.5] kg/m2, and 12.7[5.84; 19.2] vs 7.8[3.7;16.4]mg/l, accordingly, p<0.05. We didn't find differences of lipid profile, serum uric acid, and serum creatinine level in 1 and 2 group. We also didn't find differences the frequency of smoking, diabetes mellitus, subcutaneous tophi in both groups (table 1 ). Conclusion: Majority (85%) of patients with gout had AH. Abdominal obesity, family history of AH, disease duration more 10 ys, intraosseous tophi were associated with an increased risk of AH in pts with a gout. Disclosure of Interests: None declared